Autonomous detection, following and mapping of an underwater chain using sonar. (15th January 2017) - Hurtós, Natàlia; Palomeras, Narcís; Carrera, Arnau; Carreras, Marc
Abstract: Following an underwater chain using an autonomous vehicle can be a first step towards more efficient solutions for cleaning and inspecting mooring chains. We propose to use sonar as a primary perception sensor to enable the vehicle operation in limited visibility conditions and overcome the possible turbidity arising during marine growth removal. Despite its advantages, working with acoustic data raises additional challenges for the processing and control methodologies involved. We present two chain link detectors that make use of forward-looking sonar and multibeam data and we combine them with adequate planning and control strategies to achieve a robust framework to detect, follow and map an underwater chain. Experiments conducted in a water tank and in a real harbor environment demonstrate the capability of autonomously detecting and following a chain with sufficient accuracy to perform subsequent cleaning or inspection tasks. Besides this, we demonstrate the possibility of obtaining a preliminary map of the chain and its surroundings regardless of visibility conditions. Abstract : Highlights: First step towards autonomous cleaning and inspection of mooring chains. On-line detection of chain links based on forward-looking and multibeam sonar. AUV control based on real-time sonar perception. Sonar mosaic to provide first inspection of chain state and surroundings.